A new species and record of Serpulidae (Annelida: Polychaeta) from Cross Seamount in the Hawaiian Chain - Bailey-Brock, Julie H.; Magalhães, Wagner F. (Zootaxa, 2012)
A new species of the serpulid genus Metavermilia Bush, 1905 and a new record of the genus Omphalopomopsis Saint-Joseph, 1894 are described from deep-sea lava rocks collected from 2,013 m at Cross Seamount, southwest of the Hawaiiarchipelago. Metavermilia zibrowii sp. nov., differs from its congeners mostly by the presence of a simple and concaveoperculum, extent of the thoracic membrane and tube morphology. Omphalopomopsis langerhansii (Marenzeller, 1885)is the type species of the genus and it is only known through its type specimen. This species is characterized by a simpleoperculum with a shallow convex calcareous endplate, cylindrical peduncle, presence of Apomatus chaetae and high num-ber of teeth in the thoracic uncini. This is the first record of this species outside the type locality and both genera are newly recorded for the Hawaiian Islands.